Simulation and experimental characterization of microporosity during solidification in Sn-Bi alloys. (15th December 2021) - Siroky, Georg; Kraker, Elke; Kieslinger, Dietmar; Kozeschnik, Ernst; Ecker, Werner
Graphical abstract: Highlights: Investigation of microporosity during solidification of non-eutectic Sn-Bi alloys: experiments and simulation. Semi-solid material model for RVE-FEM simulation. Criterion for porosity formation based on simulation and μ-XCT data. Good correlation between experimental and simulation results. Abstract: The formation of microporosity during solidification of Sn-Bi alloys is investigated through experiments and simulations. Samples of varying composition with 20, 30, 47 and 58 wt% Bi are solidified in a copper mould and the pore fraction is measured through scanning electron microscopy. Finite element models are derived from X-ray micro computed tomography data and a material model is implemented to capture the effect of liquid pressure and volumetric swelling. The experimental assessment of solidification porosity shows a strong dependency on alloy composition. The round morphology of porosity found in the Sn-20 wt% Bi alloy indicates its formation in the terminal stage of solidification. Microporosity formation is computed by means of Finite Element simulations and the results correlate with experimental findings. The analysis confirms volumetric shrinkage in the liquid state of confined eutectic domains as the mechanism for pore formation and determines the composition dependency of Sn-Bi alloys.